Mechanism and CO2 emissions analysis of multi-solid-waste synergistic red mud-based composite cementitious materials under orthogonal tests - Lili Cheng; Daiyu Zhou; Qiwan Zhang; Lingling Wang; Ninggui Hu; Zeyuan Wang (Scientific Reports, 2025)
Abstract The large stockpile and low utilization rate of red mud (RM) have caused an urgent need for large quantities of RM to be eliminated. In this study, multi-solid-waste synergistic RM-based composite cementitious materials (MS-RMCM) were prepared using RM as the primary material, combined with fly ash, silica fume, and quicklime. Orthogonal tests were conducted to investigate the effects of cementitious components on the mechanical properties. The effect mechanisms were discussed by SEM–EDS results. The results revealed that: (1) Range analysis indicated that the factors influencing the 28 d compressive strength ranked as follows: quicklime (C) > silica fume (B) > fly ash (A). The optimal combination was determined to be A2B3C4, achieving a maximum compressive strength of 25.13 MPa with 53% RM. (2) Variance analysis revealed that F (fly ash) = 3.961 < F0.01, F(silica fume) = 17.778 > F0.01, and F(quicklime) = 61.921 > F0.01, indicating that fly ash had no significant effect on the 28 d compressive strength, while silica fume had a significant effect, and quicklime had a highly significant effect. (3) Microscopic analysis showed that the strength improvement contributed by fly ash and silica fume was mainly attributed to their good potential pozzolanic activity and microaggregate filling effect. Quicklime enhanced the compactness by generating more hydration products after activating fly ash, silica fume and RM. (4) Life cycle assessment calculations indicated that the carbon emissions of MS-RMCM were 273.01 kg/t, with a unit compressive strength carbon emission coefficient of 10.86 kg/MPa, indicating the significant advantages of MS-RMCM in reducing CO2 emissions in the construction industry.